2014
DOI: 10.1038/nprot.2014.049
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid recreation by reverse breeding in Arabidopsis thaliana

Abstract: Hybrid crop varieties are traditionally produced by selecting and crossing parental lines to evaluate hybrid performance. Reverse breeding allows doing the opposite: selecting uncharacterized heterozygotes and generating parental lines from them. With these, the selected heterozygotes can be recreated as F1 hybrids, greatly increasing the number of hybrids that can be screened in breeding programs. Key to reverse breeding is the suppression of meiotic crossovers in a hybrid plant to ensure the transmission of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 27 publications
1
35
0
1
Order By: Relevance
“…Furthermore, the HI parent produces few viable pollen 16,23 and thus we prefer to use HI as a female parent in crosses to produce haploids. F1 seed from HI Â WT crosses produce a mixture of hybrid diploids, aneuploids and haploids in addition to a high frequency of aborted seeds 16,24 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the HI parent produces few viable pollen 16,23 and thus we prefer to use HI as a female parent in crosses to produce haploids. F1 seed from HI Â WT crosses produce a mixture of hybrid diploids, aneuploids and haploids in addition to a high frequency of aborted seeds 16,24 .…”
Section: Resultsmentioning
confidence: 99%
“…Haploids can be identified by phenotypic, genotypic and cytological methods 16,24 (see Methods, Supplementary Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The suppression of meiotic crossovers and transmission of non-recombinant chromosomes to haploid gametes is a key to reverse breeding. Gametes are subsequently regenerated as doubled-haploid offspring among which the parental lines are selected (Wijnker et al, 2014). Thanks to the knowledge of the oil palm gene space (Low et al, 2014), meiosis regulators, such as DMC1orthologs (Wijnker et al, 2012) can be identified and then controlled.…”
Section: Increasing Oil Palm Productivitymentioning
confidence: 99%
“…So konnten im Rahmen einer Proof-of-Concept-Studie anhand der Modellpflanze Arabidopsis thaliana homozygote Elternlinien aus einem Hybridindividuum gewonnen werden (Wijnker et. al., 2012;Wijnker et. al., 2014).…”
Section: Reverse Breedingunclassified